Akulturasi Islam dalam bingkai peradaban dan budaya - Ali, Muhammad Fiqri (Maliki Interdisciplinary Journal, 2023)
This article is written in order to benefit literacy understanding of Islamic acculturation in the framework of civilization and culture. This study uses a literature review (library research) based on a descriptive qualitative approach. The results of the study state that the process of acculturation of Islam in Indonesia is very unique, how Islamization entered the archipelago with a long process. For example, Islam entered Java, where the majority of Javanese people were Hindus. With proof of the Hindu kingdoms standing and ruling in the land of Java. Likewise, traditions and customs with Hindu themes have become habits that are carried out. Islam came as a religion of compassion and brilliant preaching methods made Islam quickly enter, be accepted by the Javanese people. Islam merges with local culture which previously had non-Islamic values such as wayang, dance and music. All three were performed in religious ceremonies and were merged by Islam in an effort to propagate Islam. Then there are events with Islamic nuances such as mauludan, rajaban and slametan. This strategy implies that there is a symbiosis between religion and culture, gradually there is a dichotomy of religious culture in each region. This indicates that socio-cultural life is dynamic and continues to change according to the times, so that it becomes the cause of acculturation. Acculturation is a process of blending religion and culture, fusion of religious teachings into cultural customs.